Rediseño de una edificación antigua para crear un centro de eventos culturales Kichwa - Males Anrango, Hilda Fabiola (2013)
This project focuses on the modification of a republican edification from the year 1906 located in Loja city is downtown. The project splits into two stages; the first stage consists in rehabilitating the edification and the second stage involves changing the usage of the building, from a household to a hotel-boutique, through an interior design proposal. Loja is downtown has almost disappeared due to the lack of care from both the local inhabitants and the local government. In addition, the lack of interest from the owners has lead the exaggerated permit to destroy the characteristic architecture of the place. Therefore, this project aims to set an example for the local inhabitants, owners and the government, in terms of reconstruction and interior design so that they can appreciate the beauty and potential of these edifications. The job of the interior designer for this project will be based on the application of the brutalism trend, following a modern line where raw materials are used. In order to enrich the interior design, the brutalism will be merged with three major cultural aspects of the city, which are: literature, music and painting. With this concept a contrast between republican architecture and interior design will be achieved. The hotel will have leisure areas available for people who are not staying in it, so that the income of the hotel can increase. The leisure areas will comprehend a restaurant, a library and a bar-lounge.